A Ku Wideband Circularly Polarized Microstrip Antenna Array with Low Profile Crossed-Dipole Element - Haipeng Liu; Yunhua Zhang; Xiaowen Zhao (International Journal of Antennas and Propagation)
This paper presents a novel Ku wideband circularly polarized (CP) antenna array composed of crossed-dipole element (CDE) and fed through sequential rotation (SR) feeding technique. Unlike the traditional CP-CDE fed by coaxial cable that usually works at low frequencies, the proposed CDE consists of two orthogonal heart-shaped patch dipoles that can work at frequencies as high as Ku-band, at the same time achieving a larger bandwidth. A feeding structure is proposed without welding, so potential errors in the antenna assembly process can be mitigated. A 2 × 2 CP antenna array with wideband SR feeding network is designed based on the CDE to further expand the axial ratio (AR) bandwidth. The designed antenna array is fabricated using the multilayer printed circuit board (PCB) technology and measured in anechoic chamber using the planar near-field measurement facility. The measured results show that −10 dB impedance bandwidth of 44% (11.6–18.15 GHz) along with 3 dB AR bandwidth of 38.7% (12–17.65 GHz) and 3 dB gain bandwidth of 34.6% (12.2–17.3 GHz) as well as 11.02 dBic peak gain have been achieved while maintaining a lower profile.